Integration of Traditional and Digital Marketing Communication Strategies in New Student Recruitment - Abdul Haris; Selamat Riadi; Widya Nengsih; Rd. Heri Solehudin; Otom Mustomi (AMCA, 2026)
Competition among universities to attract prospective new students is now increasingly fierce, encouraging higher education institutions to adopt more comprehensive and integrated marketing communication strategies. This study aims to evaluate the effectiveness of combining conventional marketing communication strategies (such as the use of brochures, participation in educational exhibitions, and publications in print media) with digital strategies (including the use of social media, email marketing, and official websites) in increasing new student enrollment interest. This study used a mixed methods approach, with data obtained through a survey of 150 prospective students and in-depth interviews with marketing teams from five private universities. The research findings indicate that the integration of the two approaches can expand audience reach while increasing positive perceptions of the institution. Digital strategies are considered effective in creating fast and dynamic interactions, while traditional approaches continue to play a crucial role in building trust and emotional connections, particularly with prospective students' parents. The study concludes that the synergy between traditional and digital approaches can significantly enhance the effectiveness of higher education marketing campaigns.